The Profession of Content Creator in the Sharia-Compliant Creative Economy: Opportunities, Challenges, and Islamic Business Ethics on the Commercialization of Halal Content - Fitria, Tira Nur (Jurnal Ilmiah Ekonomi Islam, 2025)
This research describes the profession of content creator in the sharia-compliant creative economy including opportunities, challenges, and Islamic business ethics on the commercialization of halal content. This study employs a library research design. Content creators in the halal creative economy have diverse opportunities to produce Sharia-compliant content. They can support community needs, promote Islamic ethics, and empower the ummah. When adhering to Islamic principles, content creation is a legitimate, halal profession with strong potential for da’wah, education, and positive social impact. In Islamic economics, content creators can be known as digital entrepreneurs who contribute to the halal economy by producing and sharing knowledge, ethical values, and halal products via online platforms. They promote Islamic teachings and ethical lifestyles while avoiding prohibited elements like riba (interest) and gambling. Acting as informal da’wah agents, they ensure their income is halal by adhering to honesty, transparency, and accountability. Content creators foster halal consumerism, connect Sharia-compliant businesses with Muslim consumers, and incorporate social good, making their role both economic and moral. As key players in the Sharia-compliant creative economy, these creators act as digital preachers, educators, and entrepreneurs, sharing Islamic teachings through relatable content and monetizing via halal, ethical methods. By collaborating with halal brands, they help build a value-driven digital ecosystem that bridges tradition and modernity, empowering Muslim communities and advocating ethical media practices aligned with Maqasid al-Shariah. This profession balances economic success with spiritual fulfillment. Content creators engage in diverse niches such as Islamic education, modest fashion, halal product reviews, mental health, and finance, using platforms like YouTube and podcasts to reach wider audiences. Their work supports community needs, promotes Islamic ethics, and contributes positively to a faith-driven digital economy. Content creation is halal and legitimate when following Sharia principles, avoiding haram content, and guided by sincere intention (niyyah). Creators must maintain modesty, respect gender norms, and prevent riya’ (showing off). Despite opportunities from a growing global Muslim audience and halal market, creators face challenges including Sharia compliance, ethical-commercial balance, community criticism, limited halal monetization, and technical barriers. Navigating these demands requires resilience and innovation. Rooted in Islamic ethics—truthfulness, trust, justice, modesty, sincerity, and accountability—content creators help foster a just, value-driven economy, balancing material success with spiritual integrity and societal benefit. Supporting Sharia-compliant content creators requires clear halal guidelines, ethical training, halal sponsor connections, and transparent partnerships. Building community support, promoting halal consumer education, diversifying income, and collaborating with Islamic finance experts help creators grow responsibly and sustainably within Islamic principles.